A Faulty Prescription? Critiquing Joint Security Units after Peace Agreements in Sudan, South Sudan, and the Central African Republic. Issue 2 (3rd April 2022) - Verjee, Aly
ABSTRACT: This article critiques the prescription of joint security units called for by civil war peace agreements as a means to integrate armed forces previously in conflict. Drawing on cases from Sudan, South Sudan, and the Central African Republic, this article offers a comparative assessment of the joint security units attempted in each country. As negotiators and mediators often employ templates from other contexts, the deficits exemplified by these cases call for rethinking the practice of establishing joint units in the doctrine of military integration, as well as in the wider practice of negotiating security arrangements in peace processes.